Design and synthesis of pyrazolopyridine derivatives as sphingosine 1-phosphate receptor 2 ligands. Issue 3 (1st February 2018) - Luo, Zonghua; Yue, Xuyi; Yang, Hao; Liu, Hui; Klein, Robyn S.; Tu, Zhude
Graphical abstract: Abstract: Eleven new sphingosine 1-phosphate receptor 2 (S1PR2) ligands were synthesized by modifying lead compound N -(2, 6-dichloropyridin-4-yl)-2-(4-isopropyl-1, 3-dimethyl-1 H -pyrazolo[3, 4- b ]pyridin-6-yl)hydrazine-1-carboxamide (JTE-013) and their binding affinities toward S1PRs were determined in vitro using [ 32 P]S1P and cell membranes expressing recombinant human S1PRs. Among these ligands, 35a (IC50  = 29.1 ± 2.6 nM) and35b (IC50  = 56.5 ± 4.0 nM) exhibit binding potency toward S1PR2 comparable to JTE-013 (IC50  = 58.4 ± 7.4 nM) with good selectivity for S1PR2 over the other S1PRs (IC50  > 1000 nM). Further optimization of these analogues may identify additional and more potent and selective compounds targeting S1PR2.